Magnetic resonance cholangiopancreatography (MRCP) using new negative per-oral contrast agent based on superparamagnetic iron oxide nanoparticles for extrahepatic biliary duct visualization in liver cirrhosis - Poláková, Kateřina; Mocikova, Ingrid; Purova, Dana; Tucek, Pavel; Novak, Pavel; Novák, Pavel; Izák, Nikola; Bielik, Radoslav; Zbořil, Radek; Heřman, Miroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND AND AIMS: Magnetic resonance cholangiopancreatography (MRCP) is often used for imaging of the biliary tree and is required by surgeons before liver transplantation. Advanced liver cirrhosis and ascites in patients however present diagnostic problems for MRCP. The aim of this study was to find out if the use of our negative per-oral contrast agent containing superparamagnetic iron oxide nanoparticles (SPIO) in MRCP is helpful for imaging of hepatobiliary tree in patients with liver cirrhosis. METHODS: Forty patients with liver cirrhosis were examined on a 1.5 T MR unit using standard MRCP protocol. Twenty patients (group A) underwent MRCP after administration of per-oral SPIO contrast agent 30 min before examination. In group B, twenty patients were examined without per-oral bowel preparation. Ascites was present in eleven patients from group A and in thirteen patients in group B. Four radiologists analyzed MR images for visibility and delineation of the biliary tree. χ(2) tests were used for comparison of the visibility of intrahepatic and extrahepatic biliary ducts in patients with and without ascites. RESULTS: Better extrahepatic biliary duct visualization and visibility of extraluminal pathologies in patients with ascites was proved after administration of SPIO contrast agent. No statistically significant difference between group A and B was found for visualization of extrahepatic biliary ducts in patients without ascites. Delineation of intrahepatic biliary ducts was independent on bowel preparation. CONCLUSIONS: Application of our negative per-oral SPIO contrast agent before MRCP improves the visualization of extrahepatic biliary ducts in patients with ascites which is helpful during the liver surgery, mainly in liver transplantation.
Keywords: senioři; Contrast Media; senioři nad 80 let; jaterní cirhóza; Middle Aged; mužské pohlaví; kontrastní látky; Liver Cirrhosis; aplikace orální; žlučové cesty intrahepatální; Adult; mladý dospělý; Bile Ducts, Extrahepatic; Ferric Compounds; Cholangiopancreatography, Magnetic Resonance; Aged, 80 and over; Young Adult; ženské pohlaví; magnetická rezonanční cholangiopankreatografie; železité sloučeniny; Humans; žlučové cesty extrahepatické; Bile Ducts, Intrahepatic; lidé středního věku; Administration, Oral; dospělí; Female; Aged; Metal Nanoparticles; kovové nanočástice; lidé; Male